Biodiversity crisis or sixth mass extinction?: Does the current anthropogenic biodiversity crisis really qualify as a mass extinction?. (9th December 2021) - Rull, Valentí
Abstract : Human actions have caused an increasing number of species to go extinct. Do the available data support concerns about a new mass extinction event?